The effect of adipose-derived mesenchymal stem cell transplantation on ovarian mitochondrial dysfunction in letrozole-induced polycystic ovary syndrome in rats: the role of PI3K-AKT signaling pathway - Arash Abdi; Mina Ranjbaran; Fardin Amidi; Fariba Akhondzadeh; Behjat Seifi (BMC, 2024)
Abstract Objective The present study aimed to elucidate how mesenchymal stem cells (MSCs) application could efficiently attenuate pathological changes of letrozole-induced poly cystic ovary syndrome (PCOS) by modulating mitochondrial dynamic via PI3K-AKT pathway. Methods Thirty-two female rats were randomly divided into four experimental groups: Sham, PCOS, PCOS + MSCs, and PCOS + MSCs + LY294002. The Sham group received 0.5% w/v carboxymethyl cellulose (CMC); the PCOS group received letrozole (1 mg/kg, daily) in 0.5% CMC for 21 days. Animals in the PCOS + MSCs group received 1 × 106 MSCs/rat (i.p,) on the 22th day of the study. In the PCOS + MSCs + LY294002 group, rats received LY294002 (PI3K-AKT inhibitor) 40 min before MSC transplantation. Mitochondrial dynamic gene expression, mitochondrial membrane potential (MMP), citrate synthase (CS) activity, oxidative stress, inflammation, ovarian histological parameters, serum hormone levels, homeostatic model assessment for insulin resistance (HOMA-IR), insulin and glucose concentrations, p-PI3K and p-AKT protein levels were evaluated at the end of the experiment. Results PCOS rats showed a significant disruption of mitochondrial dynamics and histological changes, lower MMP, CS, ovary super oxide dismutase (SOD) and estrogen level. They also had a notable rise in insulin and glucose concentrations, HOMA-IR, testosterone level, tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) levels, ovarian malondialdehyde (MDA) content as well as a notable decrease in p-PI3K and p-AKT protein levels compared to the Sham group. In the PCOS + MSCs group, the transplantation of MSCs could improve the above parameters. Administration of LY294002 (PI3K-AKT pathway inhibitor) deteriorated mitochondrial dynamic markers, oxidative stress status, inflammation markers, hormonal levels, glucose, and insulin levels and follicular development compared to the PCOS + MSCs group. Conclusions This study demonstrated that the protective effects of MSC transplantation in regulating mitochondrial dynamics, promoting mitochondrial biogenesis, competing with redox status and inflammation response were mainly mediated through the PI3K-AKT pathway in the PCOS model.